2009
DOI: 10.1002/ijc.24114
|View full text |Cite
|
Sign up to set email alerts
|

An intron 4 VNTR polymorphism of the endothelial nitric oxide synthase gene is associated with early‐onset colorectal cancer

Abstract: Endothelial-derived nitric oxide, which is produced by endothelial nitric oxide synthase (eNOS), may play an important role in colorectal carcinogenesis. However, the putative contribution of common eNOS genetic polymorphisms to colorectal cancer risk remains unknown. We genotyped 3 polymorphisms of eNOS (T-786C, G894T, and intron4b/a) in 727 colorectal adenocarcinoma cases and 736 age-and sex-matched healthy controls in Taiwan. Genotypes of the T-786C and G894T polymorphisms were determined by fluorescence po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 57 publications
(115 reference statements)
3
23
0
Order By: Relevance
“…However, although with the powerful statistical analysis, we could not discover any associations in the two loci (G894T/rs1799983, T-786C/rs2070744) and CRC risk or the tumor sites and pathologic stages. According to the recent studies, the significant corrections in these two NOS3 polymorphisms were confirmed even though the reverse opinions presented, (Yeh et al, 2009;Jang et al, 2013) which promoted us to study these concerned polymorphisms further. After seeking for the essential characteristics of NOS3 gene, we found that rs1799983 was the non-synonymous mutation with splicing (ESE or ESS) function.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, although with the powerful statistical analysis, we could not discover any associations in the two loci (G894T/rs1799983, T-786C/rs2070744) and CRC risk or the tumor sites and pathologic stages. According to the recent studies, the significant corrections in these two NOS3 polymorphisms were confirmed even though the reverse opinions presented, (Yeh et al, 2009;Jang et al, 2013) which promoted us to study these concerned polymorphisms further. After seeking for the essential characteristics of NOS3 gene, we found that rs1799983 was the non-synonymous mutation with splicing (ESE or ESS) function.…”
Section: Discussionmentioning
confidence: 97%
“…When reading all the abstracts, we left over 9 papers with association of CRC risk and NOS3 gene involved (Conde et al, 2006;Ikeda et al, 2008;Funke et al, 2009a;Funke et al, 2009b;Yeh et al, 2009;Ho-Pun-Cheung et al, 2011;Kim et al, 2011;Arıkan et al, 2012;Jang et al, 2013), after excluding the articles that didn't satisfy our criteria. While reviewing all the papers, we removed 3 articles as follows: (1) two studies mainly described the radiotherapy and chemotherapy without raw data of genotypes in the CRC and control groups (Funke et al, 2009b;Ho-PunCheung et al, 2011); (2) although one study investigated the candidate genes polymorphism and CRC risk, there was no data about the each allele (Ikeda et al, 2008).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34][35][36] In studies for cancer suspectibility, it was found that eNOS 4 a/b variant is associated with colorectal cancer, prostate cancer, whereas there was no significant association with bladder cancer and overall cancers. 4,7,10,37,38 In sub-group analysis based on ethnicity of meta analysis, it was reported that the eNOS 4 a/b variant was associated with an increased risk of cancer in Caucasians. 24 In our study, we found that the the eNOS intron 4 a/b variant wasn't significantly different between patients and controls.…”
Section: Discussionmentioning
confidence: 99%